Examination of Multiplexing VDSL2 over ADSL2+ Line - Lafata, P. (Elektronika ir Elektrotechnika, 2013)
Today, the second generation of Very High Speed Digital Subscriber Lines (VDSL2) is widely used to replace previous Asymmetric Digital Subscriber Lines (ADSL2+) in access networks in practice. However, the VDSL2 lines can be usually applied only for short distances and also some of the subscribers will probably keep using their old ADSL2+ lines. Due to that, the frequency band of symmetrical pairs with ADSL2+ lines will stay unoccupied above 2.2 MHz and could be possibly used for VDSL2 lines. That is why a new idea about multiplexing VDSL2 line over ADSL2+ is investigated and described in this article. Both of these lines using one single symmetrical pair in a cable must be separated by frequency multiplexing method, when ADSL2+ line occupies frequency band up to 2.2 MHz, while the VDSL2 line would operate from 2.2 MHz to higher frequencies. The method could possibly increase the number of xDSL lines in one cable and could connect more subscribers using existing metallic lines. This article describes the initial idea together with the process of designing possible VDSL2 over ADSL2+ splitter, which was subsequently used for performing real measurements. Thanks to these measurements, simulations of several possible scenarios were performed and are presented in this article as well. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.3116